EFFECTIVENESS OF TOTAL PHYSICAL RESPONSE METHOD IN VOCABULARY LEARNING FOR BIPA LEARNERS: A LITERATURE REVIEW - Herdi; Nuny Sulistiany Idris; Ida Widia (RADJA PUBLIKA, 2025)
Vocabulary is the most important aspect and also the main foundation in Bahasa Indonesia bagi Penutur Asing (BIPA) or Indonesian as a Foreign Language (IFL) to foreign learning to improve foreign language skills including listening, speaking, reading and writing skills. In practice, remembering and using new vocabulary is still an obstacle for foreign learners in communicating, so there needs to be an appropriate learning method to overcome this, namely by using the Total Physical Response (TPR) method, a method that connects commands, speech and movement. This article was written using the literature review method by analyzing 10 national and international studies related to the effectiveness of the TPR method in learning. Based on the research that has been analyzed, it shows that the TPR method makes learning more effective; makes learners feel happy, enthusiastic and actively participates during the learning process; effective for speaking and writing skills; motivates children to be interested in learning, especially training listening; improves vocabulary skills from the cognitive, affective and psychomotor domains; helps learners learn vocabulary and makes learners more active and confident; learning becomes fun, learners become more active, helps students remember and improve word mastery; has a significant good influence, namely it can improve understanding, practice, respond, mention and show various types of vocabulary that have been learned; improve vocabulary process and mastery; able to improve children's motor skills; and make learners quickly master learning materials.